Pengaruh Penerapan Media Video Terhadap Hasil Belajar Menulis Puisi Siswa Sekolah Dasar Inpres 6/75 Kabupaten Bone - Rukayah, Rukayah; Rosmalah, Rosmalah; Kadir, Abd (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study was conducted to determine the effect of the application of video on the learning outcomes of students' poetry writing at SD Inpres 6/75 Manurunge, Tanete Riattang District, Bone. This research uses quasi-experimental research. The research variable was video as the independent variable and the result of learning to write poetry as the dependent variable. The research design used was pre-experimental with one group pretest-posttest design. The population in this study were fifth-grade students of SD Inpres 6/75 Manurunge, Tanete Riattang Bone District. Researchers used saturated census/sampling. The research location is SD Inpres 6/75 Manurunge, TaneteRiattang District, Bone. Data collection was done by testing, before and after treatment. The data obtained from the test were analyzed using descriptive statistical techniques and inferential statistical techniques using SPSS 24.00 for windows. The results showed that there was a significant difference between students' learning outcomes to write poetry before and after the application of video in writing poetry at SD Inpres 6/75 Manurunge, Tanete Riattang District, Bone. This difference can be seen from the quality of learning outcomes after applying video better than before applying video in learning. The conclusion is that video has a positive effect on student learning outcomes at SD Inpres 6/75 Manurunge, Tanete Riattang District, Bone. The amount of the contribution of video through students' learning achievement to write poetry was 27.8% with a fairly good category, 72.2% was influenced by other variables.